Molecular docking-guided optimisation of an Aloe Vera-Based buccal protein delivery system - Huay, Chin Heng; Rehman, Khurram; Mohd Hanif Zulfakar (Penerbit Universiti Kebangsaan Malaysia, 2025)
Proteins play vital roles in the body and are frequently used as therapeutic agents, yet their efficacy is often hindered by issues like stability and poor bioavailability. The buccal drug delivery system offers a promising alternative by directly administering medications through the cheek’s mucosal lining, bypassing the digestive tract and enhancing absorption into the bloodstream. In this study, sodium carboxymethyl cellulose (SCMC) and chitosan (CHI) films were prepared for albumin buccal delivery and were characterized for their mechanical strength and later optimized with the help of molecular docking studies. SCMC films exhibited significantly higher albumin release (71.09 ± 8.61 μg/cm2) compared to CHI films (38.38 ± 5.15 μg/cm2) and both formulations showed compliance with the Korsemeyer-Peppas model (R2 approaching ≈ 0.99, n = 0.65) indicating non-Fickian diffusion as a dominant mechanism of drug permeation. Molecular docking studies were instrumental in guiding the design of the optimized formulation for albumin buccal drug delivery, providing insights into molecular interactions and facilitating the rational refinement of albumin-polymer delivery systems. The molecular docking studies showed interactions between albumin and polymers, with stronger hydrogen bonding observed between certain residues of the polymers and albumin, particularly SER-419 and GLU-505 in SCMC and LEU-112, ASN-109, and ASN-111 in chitosan. These findings contribute to understanding the mechanisms underlying drug release and binding interactions, facilitating the development of more effective drug delivery systems, ultimately leading to more efficient and targeted therapeutic interventions.